2022
DOI: 10.1021/acs.jafc.1c07754
|View full text |Cite
|
Sign up to set email alerts
|

Glycerophospholipidomics of Five Edible Oleaginous Microgreens

Abstract: Microgreens are a special type of vegetal product, born as a culinary novelty (traditionally used to garnish gourmet dishes) and then progressively studied for their potentially high content in nutraceuticals, like polyphenolic compounds, carotenoids, and glucosinolates, also in the perspective of implementing their cultivation in space stations/colonies. Among further potential nutraceuticals of microgreens, lipids have received very limited attention so far. Here, glycerophospholipids contained in microgreen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
27
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(30 citation statements)
references
References 59 publications
3
27
0
Order By: Relevance
“…20 The high mass resolution provided by such platforms allows the distinction of lipid ions that exhibit very slight differences in their theoretical m/z ratio, 21 and accurate m/z values can be employed to identify lipid molecules at the species level. 22 As shown in our previous study, 15 the reliability of HRMSbased studies can be supported by the adoption of a preliminary chromatographic separation. In the case of glycerophospholipids, hydrophilic interaction liquid chromatography (HILIC) separations, based on polar stationary phases, represent a very effective approach, since they provide a class-related separation.…”
Section: Introductionmentioning
confidence: 61%
See 1 more Smart Citation
“…20 The high mass resolution provided by such platforms allows the distinction of lipid ions that exhibit very slight differences in their theoretical m/z ratio, 21 and accurate m/z values can be employed to identify lipid molecules at the species level. 22 As shown in our previous study, 15 the reliability of HRMSbased studies can be supported by the adoption of a preliminary chromatographic separation. In the case of glycerophospholipids, hydrophilic interaction liquid chromatography (HILIC) separations, based on polar stationary phases, represent a very effective approach, since they provide a class-related separation.…”
Section: Introductionmentioning
confidence: 61%
“…Interestingly, the tandem MS (MS/MS) structural characterization of GPLs showed that the FAC 18:3 (i.e., a fatty acyl chain with 18 carbon atoms and 3 DB equivalents) was the most diffused fatty acyl unit in the main GPL classes encountered in chia and flax microgreens. 15 However, no information was retrieved for less polar lipid classes, such as TGs and SEs, that might also represent a source of that fatty acyl chain. Moreover, despite the recognition of 18:3 fatty acyl chains suggesting the possible presence of ALA, a confirmation could not be obtained since no additional evidence was provided to unveil the position of carbon−carbon double bonds.…”
Section: Introductionmentioning
confidence: 99%
“…BM have a fat content of less than 1 g/100 g FW, which enables their users to produce foods with low-fat contents. The contents of protein, total carbohydrates and calories in BM are lower compared to Fabaceae microgreens, according to Kowitcharoen et al BM are also a source of essential fatty acids that are not produced by the human body but are vital for human health . In the Brassica carinata microgreens, Nakakaawa et al reported that α-linoleic acid and linoleic acid were the most abundant compounds along with other fatty acid such as ethyl linolenate and palmitic acid.…”
Section: Composition Of Bmmentioning
confidence: 99%
“…In the Brassica carinata microgreens, Nakakaawa et al reported that α-linoleic acid and linoleic acid were the most abundant compounds along with other fatty acid such as ethyl linolenate and palmitic acid. The highest amount of phosphatylcholines and phosphatidylethanolamines, the main glycerophospholipids, have been detected in the rapeseed microgreens . Despite the tremendous health property functions of amino acids and fatty acids, few studies have addressed the presence and amount of these organic compounds in BM.…”
Section: Composition Of Bmmentioning
confidence: 99%
See 1 more Smart Citation